Characterising road infrastructure indicators on distance and affordable housing / Muhamad Hilmi Mohamad @ Masri ... [et al.] - Mohamad @Masri, Muhamad Hilmi; Sa’ad, Mohd Farid; Azman, Najma; Aliasak, Mohd Hasrol Haffiz; Md Wadzir, Mohamad Fitry (2021)
The research aims the road infrastructure indicators and study the relationship of distance and also affordable housing in the northern region of Peninsular Malaysia. The objectives of this research are to measure road infrastructure indicators relating to distance and affordable housing, and also to analyse the relationship between road infrastructure indicators on distance and affordable housing. The instrument to gather the data needed was through the questionnaire survey that has been carried out through the usage of Google Form and achieved the sampling of about 50 respondents. The questionnaire consists of 5-Point Likert Scale, together with the indicators of traffic number, cost of commute, vehicle mobility, travel time, workplace distance, road network distance, and several affordable houses. These indicators were derived from the earlier literature review. The obtained responses will be analysed using the Structural Equation Modelling, and the findings will be discussed on the relationship between the indicators and the purchasing of affordable houses. The secondary data to measure the relationship will be obtained from affordable housing prices in Perak. The recommendations will benefit commuters in deciding to purchase houses with suitable distances from their workplaces. These commuters, therefore, can help to increase their quality of life through quality houses that correlate with acceptable distances that they have to commute every day.